2014
DOI: 10.3748/wjg.v20.i22.6912
|View full text |Cite
|
Sign up to set email alerts
|

Serum adipokines in inflammatory bowel disease

Abstract: IBD modulates serum adipokine levels by increasing resistin and visfatin release and suppressing leptin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 31 publications
6
68
1
4
Order By: Relevance
“…In this cohort study, involving patients with active UC, we compared levels before treatment of the flare with anti‐inflammatory and/or immunosuppressive therapy, and the post‐treatment remission phase and a healthy control group. Unlike other studies, treatment decreased visfatin levels in the remission group . Although not diagnostic, elevation of CRP and ESR in IBD are well‐known markers for determining and monitoring disease activity.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this cohort study, involving patients with active UC, we compared levels before treatment of the flare with anti‐inflammatory and/or immunosuppressive therapy, and the post‐treatment remission phase and a healthy control group. Unlike other studies, treatment decreased visfatin levels in the remission group . Although not diagnostic, elevation of CRP and ESR in IBD are well‐known markers for determining and monitoring disease activity.…”
Section: Discussionmentioning
confidence: 71%
“…Baseline serum concentrations of visfatin were significantly higher in subjects with UC than in healthy controls. None of the previously reported studies, between active and inactive groups, failed to detect a significant difference in visfatin levels . In this cohort study, involving patients with active UC, we compared levels before treatment of the flare with anti‐inflammatory and/or immunosuppressive therapy, and the post‐treatment remission phase and a healthy control group.…”
Section: Discussionmentioning
confidence: 94%
“…2010; Waluga et al. 2014). Similarly, in our study neither the DSS-induced decrease in circulating total chemerin for all mice nor the overall higher circulating chemerin in older versus younger mice appeared to have any impact on the disease progression or severity.…”
Section: Discussionmentioning
confidence: 99%
“…Both Crohn’s disease and ulcerative colitis are associated with high levels of 2 adipokines (resistin and visfatin) and low levels of a third adipokine (leptin). 76 Another study showed that active Crohn’s disease was associated with significantly lower adiponectin levels compared with the control group. 77 Given the contradictory data in these 2 studies, the significance of these adipokine levels still is unclear.…”
Section: Small Intestinementioning
confidence: 99%